Some Pseudoparabolic Variational Inequalities with Higher Derivatives - Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider a pseudoparabolic variational inequality with higher derivatives. We prove the existence and uniqueness of a solution of this inequality with a zero initial condition.